Preliminary evidence of altered steroidogenesis in women with Alzheimer's disease: Have the patients "OLDER" adrenal zona reticularis? - Vaňková, Markéta; Hill, Martin; Velíková, Marta; Včelák, Josef; Vacínová, Gabriela; Dvořáková, Kateřina; Lukášová, Petra; Vejražková, Daniela; Rusina, Robert; Holmerová, Iva; Jarolímová, Eva; Vaňková, Hana; et al. (The Journal of steroid biochemistry and molecular biology, 2016)
Alzheimer's disease (AD) represents more than half of total dementias. Various factors including altered steroid biosynthesis may participate in its pathophysiology. We investigated how the circulating steroids (measured by GC-MS and RIA) may be altered in the presence of AD. Sixteen women with AD and 22 age- and BMI-corresponding controls aged over 65 years were enrolled in the study. The steroid levels (47 steroids and steroid polar conjugates) and their ratios in AD female patients indicated increased CYP11A1 activity, weakened activity of the CYP17A1C17,20 lyase metabolic step and attenuated sulfotransferase SULT2A1 activity at higher activity of the CYP17A1 17-hydroxylase step. The patients showed diminished HSD3B2 activity for C21 steroids, abated conversion of 17-hydroxyprogesterone to cortisol, and significantly elevated cortisol. The women with AD had also attenuated steroid 7α-hydroxylation forming immunoprotective Δ(5)-C19 steroids, attenuated aromatase activity forming estradiol that induces autoimmunity and a shift from the 3β-hydroxy-5α/β-reduced C19 steroids to their neuroinhibitory and antiinflammatory GABAergic 3α-hydroxy- counterparts and showed higher levels of the 3α-hydroxy-5α/β-reduced C21 steroids and pregnenolone sulfate (improves cognitive abilities but may be both protective and excitotoxic). Our preliminary data indicated functioning of alternative "backdoor" pathway in women with AD showing higher levels of both 5α/β-reduced C21 steroids but reduced levels of both 5α/β-reduced C21 steroids, which implied that the alternative "backdoor" pathway might include both 5α- and 5β-reduced steroids. Our study suggested relationships between AD status in women based on the age of subjects and levels of 10 steroids measured by GC-MS.
Keywords: Sulfotransferases; Steroid metabolome; hormony; Zona Reticularis; Oxidoreductases; Alzheimer’s disease; progesteronreduktasa; plynová chromatografie s hmotnostně spektrometrickou detekcí; Alzheimerova nemoc; Alzheimer Disease; Aged; senioři; oxidoreduktasy; sulfotransferasy; Gas Chromatography-Mass Spectrometry; Women; Hormones; systém (enzymů) cytochromů P-450; lidé; ženské pohlaví; RIA; Cytochrome P-450 Enzyme System; Humans; zona reticularis; Multivariate statistics; Progesterone Reductase; Female; GC–MS